Carbon footprint of different agricultural systems in China estimated by different evaluation metrics. (10th July 2019) - Huang, Jianxiong; Chen, Yuanquan; Pan, Jian; Liu, Wuren; Yang, Guangli; Xiao, Xiaoping; Zheng, Hongbing; Tang, Wenguang; Tang, Haiming; Zhou, LiJun
Abstract: Increase of concentrations of greenhouse gases (GHGs) in atmosphere have garnered lots of attention due to the associated risk of global warming. Carbon footprint (CF) is a measure that is extensively used to assess the contribution of an individual, event, organization, or product to global climate change. In the current study, the CF of five agricultural systems with different crop systems in different regions in China was evaluated in terms of CO2 eq per hectare, per kg crop yield, and per unit economic output, association with soil GHGs, agrochemical production and soil organic carbon (SOC) change. The results showed that direct nitrous oxide accounted for 61.9–97.8% of total soil GHG emissions in upland fields (agroforestry system, summer maize-winter wheat rotation tillage system, maize-soybean intercropping system, and continuous maize tillage system), while soil methane accounted for 89.9–95.1% of total soil GHG emissions in the paddy field (double rice-winter crop rotation system). GHGs produced from agricultural inputs varied from 2698.7 to 9781.5 kg CO2 eq ha −1 yr −1 among different agricultural systems. Nitrogen fertilizer was the dominant source of GHGs, which accounted for 47.4–92.4% of the total emission. Annual SOC increase ranged from −639.9–13823.9 kg CO2 eq ha −1 yr −1 in the five agricultural systems. Increases of SOC in the treatment of "reduced tillage with straw return" offset all of the total GHG emissions while "conventional tillage without straw return" decreased SOC storage in the continuous maize tillage system. An increase of SOC in crop systems of the other four agricultural systems could offset 23.2–66.7% of the total GHG emissions. Carbon emissions per hectare in the double rice-winter crop rotation system (7339.93–22994.17 kg CO2 eq ha −1 yr −1 ) were higher than the other four agricultural systems (−744.96–6523.12 kg CO2 eq ha −1 yr −1 ). In terms of crop yield, CFs of the summer maize-winter wheat rotation tillage system (0.28–0.34 kg CO2 eq kg −1 yr −1 ) were lower than those from the other four agricultural systems (0.39–2.83 kg CO2 eq kg −1 yr −1 ), except for the treatment with reduced tillage and residue return in the continuous maize tillage system. Similarly, CFs, as quantified via per unit economic output of the agroforestry system (0.12–0.19 kg CO2 eq ¥ −1 yr −1 ), were lower than those in other the four systems (0.26–0.89 kg CO2 eq ¥ −1 yr −1 ).Different evaluation methodology greatly affected the CF of different crop systems and mostly likely contributed to the contrary evaluation results, especially in the complex system of various crop systems (agroforestry and double rice-winter crop rotation system) in current study. Evaluation results of the CF of an agricultural system depends highly on the methodology used and may suggest different management decisions for lowering CF to promote the development of cleaner production. Highlights: The carbon footprint (CF) of various crop systems was evaluated via three functional units. Soil CH4 and N inputs account for most of the CF of paddies and upland fields, respectively. Increase in soil organic carbon could offset most of the total greenhouse gas emissions. Using different metrics may contribute to contradictory carbon footprint results. Assessing the CF associated with economic output is suggested for the different crop systems.